Impact of metal sulphides and partially reduced graphene oxide as a counter electrode on hybrid quantum dot sensitized solar cells performance - Sawsan A. Mahmoud; Asmaa F. Mansour; Moustafa E. Elsisi (Scientific Reports)
Abstract In the present work, different photoanodes, namely Zinc Oxide (ZnO), Cadmium Oxide (CdO), and Titanium Oxide (TiO2) nanoparticles, were deposited on fluorine-doped tin oxide (FTO) by the blade-coating method. Different quantum dots (QDs) like Cadmium Sulphide (CdS) and Zinc Sulphide (ZnS) were deposited on the photoanode by using the successive ionic layer adsorption and reaction (SILAR) technique. In this concept, different metal sulphides such as NiS, Z0.76Co0.24S, CoNi2S4, and partially reduced graphene oxide (P-rGO) were coated on the FTO substrate, which act as counter electrodes. These metal sulphides were prepared in one-step hydrothermal synthesis and Partially reduced graphene oxide (P-rGO) was synthesized from the graphite powder according to the modified Hummers and Offman method for applying as a counter electrode in quantum dot sensitized solar cells QDSSCs. The structural, electrical, and optical properties of photoanodes and counter-electrodes were investigated. The J-V characteristics of quantum dot-sensitized solar cells and the other parameters were analyzed. The power conversion efficiency of different photoanodes and different counter electrodes was compared. As P-rGO is applied as a counter electrode in a hybrid quantum dot sensitized solar cells, it enhances a photovoltaic performance of the cell 6.8% improvement compared with Z0.76Co0.24S as a counter electrode. This is due to the good electrical properties of P-rGO. Due to the well separation between the light-generated electrons and the formed holes, the cell containing TiO2 QDs with six layers of CdS QDs deposited on six layers of ZnS QDs as a hybrid structure and P-rGO as a counter electrode has the highest efficiency of 10.75% and the current density of 22.07 mA cm− 2 compared with other cells due to the wide band gap energy of TiO2 QDs that absorbed a wide range of the spectrum. So, P-rGO is a good material to achieve the high-power conversion efficiency in this type of hybrid quantum dot sensitized solar cells (HQDSSCs).